Effect of storage tempeature and seed moisture contents on papaya (Carica papaya L) seed viability and germination - Zulhisyam, A.K.; Seng, C.T.; Ismail, A.A.; Azwanida, A.A.; Shazani, S.; jamaludin, M.H. (Universiti Malaysia Terengganu, 2013)
This experiment examined the suitable storage temperature and seed moisture content for seed storage of papaya (Carica papaya L.) cultivar of “sekaki”. The seeds were dried to 6%, 8% and 10% moisture contents using silica gel and stored at 0ºC, 4ºC and 28ºC for three months. Seeds containing 6% moisture content and stored at 0ºC gave higher percentage of germination, lower dormancy, lower seed death compared to the seed of the other storage conditions. The result suggested that such condition was the best condition for papaya seed storage. Seeds containing 10% moisture content and stored at 28ºC is not recommended for papaya seed storage because seed deterioration rate under such condition is higher within three months of storage.